Consultation, negotiation and compromise: the relationship between SENCos, parents and pupils with SEN. Issue 1 (February 2016) - Maher, Anthony
Abstract : One outcome of the UK Government's commitment to inclusive educational policies was an increase in the number of pupils with special educational needs (SEN) being taught in mainstream schools. From the perspective of SENCos, this article analyses whether parents and pupils are able and willing to influence the development of SEN provision and distribution of SEN resources, both of which aim to ensure that pupils have more meaningful experiences of mainstream education. The findings of the study cast light on the power and influence of parents when it comes to SEN provision and resources, the importance of consulting parents and the ways in which parents empower SENCos to make decisions on behalf of themselves and their children. The importance of negotiating and attempting to seek a compromise with pupils was another key issue identified in the article. Ultimately, however, the power to decide where resources go and what is done with them appears to reside with SENCos.